EFEKTIVITAS PROGRAM KELUARGA HARAPAN (PKH) DI KELURAHAN ROWOSARI KECAMATAN TEMBALANG KOTA SEMARANG - Najidah, Nurul; Lestari, Hesti (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2019)
Rowosari village is a village included in the classification of the poor population highest in Tembalang Subdistrict. Family Hope Program (PKH) present since 2013 aims to reduce the number of poverty. This research aims to analyze the effectiveness of the Family Hope Program (PKH) in Rowosari Village Tembalang Subdistrict Semarang City. The research method used is a descriptive qualitative method with data collection techniques of observation, interviews, and documentation. Determination of research subjects using purposive sampling technique and the data validity use triangulation techniques. The criteria for the effectiveness of who used is the accuracy of the target, the accuracy of the purpose, the accuracy of the cost and the accuracy of think. In addition also be seen from the effectiveness of that. The results of the study showed that the accuracy of target, the accuracy of the purpose, the accuracy of the cost in the family hope program (PKH ) has not been fully effective, because there are still obstacles in its implementation, meanwhile in the accuracy of think already operating well. Factors that hinder the effectiveness of the program were there was no coordination, has been no planning and have not run the accuracy of service. Recommendations that can be given is improved coordination between stakeholders in family hope program in order to keep the appropriateness between the data on reality, created the clear goals and expected to the creation of policies on transparency in the use of funds to the achievement of the effectiveness Family Hope Program in Rowosari Village.